2010
DOI: 10.1021/nl101168u
|View full text |Cite
|
Sign up to set email alerts
|

Branched Silver Nanowires as Controllable Plasmon Routers

Abstract: Using polarization dependent scattering spectroscopy, we investigate plasmon propagation on branched silver nanowires. By controlling the polarization of the incident laser light, the wire plasmons can be routed into different wire branches and result in light emission from the corresponding wire ends. This routing behavior is found to be strongly dependent on the wavelength of light. Thus for certain incident polarizations, light of different wavelength will be routed into different branches. The branched nan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
262
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 278 publications
(263 citation statements)
references
References 33 publications
0
262
1
Order By: Relevance
“…17 Complete loss compensation and net output amplification of SPPs in strip waveguides of gold have been realized via an optical gain medium by De Leon and Berini, 19 and more recently by Kena-Cohen et al 20 However, to date there exists no demonstration of optical gain for subwavelength-confined SPPs like those in metallic NWs, despite the fact that plasmon waveguiding in 1D silver and gold NWs is well documented. [8][9][10][11][12][13][26][27][28] Chemically synthesized metal NWs with lateral dimensions of ~100 nm have emerged as an important class of plasmonic waveguides [8][9][10][11]27,28 supporting strongly confined SPPs. SPP propagation lengths in NWs are significantly enhanced compared to polycrystalline waveguides prepared lithographically because of reduced defect scattering and leakage radiation.…”
Section: Subwavelength Confinement and Active Control Of Light Is Essmentioning
confidence: 99%
See 1 more Smart Citation
“…17 Complete loss compensation and net output amplification of SPPs in strip waveguides of gold have been realized via an optical gain medium by De Leon and Berini, 19 and more recently by Kena-Cohen et al 20 However, to date there exists no demonstration of optical gain for subwavelength-confined SPPs like those in metallic NWs, despite the fact that plasmon waveguiding in 1D silver and gold NWs is well documented. [8][9][10][11][12][13][26][27][28] Chemically synthesized metal NWs with lateral dimensions of ~100 nm have emerged as an important class of plasmonic waveguides [8][9][10][11]27,28 supporting strongly confined SPPs. SPP propagation lengths in NWs are significantly enhanced compared to polycrystalline waveguides prepared lithographically because of reduced defect scattering and leakage radiation.…”
Section: Subwavelength Confinement and Active Control Of Light Is Essmentioning
confidence: 99%
“…9,10 Apart from their waveguiding properties, studied extensively by near-field 10,13 and fluorescence-based imaging techniques, [26][27][28] coupled NW structures have been shown to exhibit device functionalities such as nanoscale routers, modulators and logic elements. 12,29 Despite reduced radiative losses, SPPs in chemically prepared NWs still suffer from absorptive losses (on the order of -0.4 dB µm -1 at 800 nm) because of strong confinement. 27 These losses represent an impediment toward the realization of integrated plasmonic circuitry.…”
Section: Subwavelength Confinement and Active Control Of Light Is Essmentioning
confidence: 99%
“…The former could overcome the traditional diffraction limit in dielectric optics and be the key approach to overcoming the bottleneck of the miniaturization of nanophotonic devices and large-scale on-chip integrated circuits for next-generation information technology. [5][6][7][8][9][10][11] The extremely enhanced EM field caused by the latter has great application values in various fields, such as surface-enhanced spectrum, [12][13][14][15] surface plasmon resonance sensors, [16][17][18][19] ultra transmission, 20,21 plasmonic trapping, 22,23 plasmonic-enhanced emission, 24,25 quantum communication, 26,27 super-resolution microscopy, 28 cloaking, 29 photothermal cancer therapy, 30,31 steam generation, 30,32,33 holography, 34 photovoltaics [35][36][37] and water splitting. [38][39][40] One of the most promising applications of SPPs, especially localized SPPs, is surface-enhanced Raman scattering (SERS), which has been studied both theoretically and experimentally for many decades.…”
Section: Introductionmentioning
confidence: 99%
“…These have been used in a wealth of applications from flexible/stretchable electronics 14,15 to plasmonic applications such as surface-enhanced Raman spectroscopy (SERS) 16 and subwavelength optoelectronics. 17 Compared with bulk silver, crystalline AgNWs have improved mechanical properties. Strain−stress measurements have revealed that the Young's modulus of AgNWs benefits from the stiffening size effect 18 and can reach 160 GPa, 19,20 which is 3 times larger than bulk silver and exceeds that of silicon nanowires.…”
Section: Nano Lettersmentioning
confidence: 99%